Meeting the Language Needs of Emergent Multilingual Students at Risk for Learning Disabilities through Multitiered Systems of Support. Issue 3 (14th August 2022) - Artzi, Lauren; Hsin, Lisa B.; Sanford, Amanda K.; Brown, Julie Esparza; Guin, Swati
Abstract: This review and case example describes the key components of elementary reading instruction and intervention within multitiered systems of supports (MTSS) and ways to enhance and scaffold reading instruction and intervention for language as a means of supporting the learning of students who are emergent multilingual (EM) learners. First, we provide an overview of elementary reading comprehension skills and describe culturally, linguistically, and ecologically situated learning principles and overview the essential elements of MTSS rooted in these principles. Next, we present research‐based practices that enhance reading instruction and intervention among elementary EM students. We then illustrate the PLUSS framework to highlight how educators can implement these practices across MTSS. Finally, we present considerations for reading instruction and intervention and provide resources that may be useful to educators and policymakers with respect to MTSS.